Dispersion Homogeneity and Electrochemical Performance of Si Anodes with the Addition of Various Water-Based Binders. Issue 10 (20th July 2018) - Huang, Ling-Hsuan; Chen, Di; Li, Chia-Chen; Chang, Yu-Lung; Lee, Jyh-Tsung
Abstract : Four binders, sodium alginate (SA), guar gum (GG), carboxymethyl cellulose (CMC), and a mixture of styrene-butadiene rubber (SBR) and CMC, are used for aqueous processed Si anodes, and the effects of their addition on the homogeneity of dispersion, electrode adhesion properties, and cell performance of constructed lithium-ion batteries are compared. The addition of CMC not only leads to the best dispersion of the electrode constituents, but also provides the best adhesion for the electrode on the current collector and the best cycle life and rate capability; these properties are better than those found when using the more popular binders SA and GG. Although the Si active powder used in this investigation is micro-sized, a battery using CMC as the binder in the Si anode achieves high capacities of 2930 and 1380 mAh g −1 at currents of 420 and 3360 mA g −1, respectively, during delithiation. Interestingly, with the combined use of CMC and SBR, the mentioned properties deteriorate significantly; this is primarily attributed to the increased impedance caused by the poor distribution of SBR in the electrode.